Respuesta :
The equation of the circle that passes through the given points and has its center lying on this line 2x + y = 7 is equal to x² + y² - 10x + 6y - 6 = 0.
The equation of a circle.
Mathematically, the standard form of the equation of a circle is given by;
(x - h)² + (y - k)² = r²
Where:
- h and k represents the coordinates at the center.
- r represents the radius of a circle.
How to determine the equation of this circle?
Assuming the center of this circle lies at (h, k), then we have the following expressions that models the distance from the center of the given circle:
(h - 7)² + (k - 3)² = (h - 11)² + (k - (-1))²
(h - 7)² + (k - 3)² = (h - 11)² + (k + 1)²
(h - 7)² - (h - 11)² = (k + 1)² - (k - 3)²
(h - 7 + h - 11)(h - 7 - h + 11) = (k + 1 + k - 3)(k + 1 - k + 3)
(2h - 18)(4) = (2k - 2)(4)
8h - 72 = 8k - 8
8h - 8k = 64
h - k = 8 .......equation 1.
Since (h, k) lies at 2x + y = 7, we have:
2h + k = 7 .......equation 2.
Solving eqn. 1 and eqn. 2 simultaneously, we have:
h - k = 8
2h + k = 7
3h = 15
h = 15/3
h = 5.
For the value of k, we have:
h - k = 8
5 - k = 8
k = 5 - 8
k = -3.
Next, we would determine the radius of this circle:
Radius, r² = (h - x)² + (k - y)²
Radius, r² = (5 - 7)² + (-3 - 3)²
Radius, r² = (-2)² + (-6)²
Radius, r² = 4 + 36
Radius, r = √40.
Now, we can write the equation of this circle:
(x - h)² + (y - k)² = r²
(x - 5)² + (y - (-3))² = 40
(x - 5)² + (y + 3)² = 40.
x² - 5x - 5x + 25 + y² + 3y + 3y + 9 - 40 = 0
x² - 10x + 25 + y² + 6y - 31 = 0
x² - 10x + y² + 6y - 6 = 0
x² + y² - 10x + 6y - 6 = 0.
Read more on equation of a circle here: https://brainly.com/question/24307696
#SPJ1